2021
DOI: 10.1021/acs.jafc.1c05338
|View full text |Cite
|
Sign up to set email alerts
|

Ripened Pu-Erh Tea Improved the Enterohepatic Circulation in a Circadian Rhythm Disorder Mice Model

Abstract: Glucolipid metabolism, nitrogen metabolism, and inflammation are closely related to circadian rhythm disorder (CRD). Ripened Pu-erh tea (RPT) shows significant antidyslipidemic, antihyperurecemic, and anti-inflammatory effects. However, it is unclear whether healthy population are affected by CRD and whether long-term consumption of RPT can alleviate it. To investigate this problem, healthy mice were pretreated with RPT (0.25%, w/v) for 60 days and then subjected to CRD for 40 days. Our results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…There are relatively few studies on the abundance of norank_f_Muribaculaceae . It improved the structure of intestinal flora and abundance in alcohol-drinking rats after Pu’erh tea intervention, which agreed with the changing trend of this study [ 49 ]. Clostridium has been proved to be an important bacterium for the formation of amino acids [ 44 , 50 ] and has an effect on the amino acid content in intestinal tissues, liver, and other tissues.…”
Section: Discussionsupporting
confidence: 88%
“…There are relatively few studies on the abundance of norank_f_Muribaculaceae . It improved the structure of intestinal flora and abundance in alcohol-drinking rats after Pu’erh tea intervention, which agreed with the changing trend of this study [ 49 ]. Clostridium has been proved to be an important bacterium for the formation of amino acids [ 44 , 50 ] and has an effect on the amino acid content in intestinal tissues, liver, and other tissues.…”
Section: Discussionsupporting
confidence: 88%
“…It seems a there is a possible involvement of the gut-liver axis through the LPS/TLR-4/pro-inflammatory cytokines axis in the pathogenesis of inflammatory processes. Our lab's early studies have shown that the reduction of intestinal inflammation and liver toxicity by tea (Camella sinensis) and hawk tea (Litsea coreana) is due to the reshaping of gut microbes [17,23,54,84], which further supported the finding reported in this paper that the ALD-mediated intestinal microorganism composition affects intestinal and liver inflammation. The intestinal-flora-disorder-mediated activation of TLR4 signaling pathways aggravates lipid metabolic disorders, further causing liver lipid deposition.…”
Section: Discussionsupporting
confidence: 84%
“…Our experimental results showed that the intestinal flora of ALD-model mice were broken and promoted inflammatory factors. Inflammatory factors and the bacteria invaded the liver through enterohepatic circulation, and then aggravated the hepatic inflammatory and lipid metabolism disorders, before finally accelerating fatty liver and liver fibrosis [84]. Increased TLR-4 and pro-inflammatory cytokines (IL1β, IL6, TNF-α) levels were detected in ALD-model mice; this was associated with bacterial overgrowth or microbiota changes as well as increased intestinal permeability [3].…”
Section: Discussionmentioning
confidence: 99%
“…After a one-week adaptation period, the mice were randomly divided into the W group (drinking water) and the T group drinking 0.25% (w/v) Pu-erh tea (an equivalent dose of human consumption of 7 g/60 kg/day). 22 After feeding for 7 weeks, each group was randomly divided into four groups, CK-T, CK-W, CRD-T, and CRD-W, respectively. Among them, CK-T and CK-W continued to receive normal light treatment (LD 12:12), while CRD-W and CRD-T were with the CRD schedule [6 h advance of the LD12:12 cycle every 5 days] (Figure 1A).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Our earlier research found that Pu-erh tea extracts could alleviate glucolipid and nitrogen metabolism in CRD-induced mice by modulating bile acid-mediated enterohepatic circulation. 22 However, it is insufficient to evaluate whether Pu-erh tea alleviates dizziness, sleepiness, and mental depression after staying up late. In recent years, tryptophan metabolism has shown the potential to improve neurodegenerative diseases and metabolic diseases.…”
Section: ■ Introductionmentioning
confidence: 99%